Comparing the effects of thermal and non-thermal technologies on pomegranate juice quality: A review. (1st May 2019) - Putnik, Predrag; Kresoja, Željka; Bosiljkov, Tomislav; Režek Jambrak, Anet; Barba, Francisco J.; Lorenzo, Jose M.; Roohinejad, Shahin; Granato, Daniel; Žuntar, Irena; Bursać Kovačević, Danijela
Highlights: Thermal processing damages nutritional and visual appeal of the pomegranate juice. Non-thermal technologies for preservation pomegranate juice is discussed. Ultraviolet-C, high-pressure, ultrasound, pulsed electric field, cold plasma. Abstract: The consumption of pomegranate juice (PJ) has increased substantially since scientific literature reported its therapeutic benefits that are attributable to antioxidant, antimicrobial, anti-carcinogenic, and anti-inflammatory properties. The growing consumer demands for fresh and high-quality food products have led to the interest in non-thermal technologies for preservation of fruit juices. Although thermal pasteurization is the most widely used preservation technology, it has adverse effects on the nutritional and sensory quality of juices. Conversely, non-thermal technologies are suitable alternatives for preservation and without negative effects on the quality. However, there is limited scientific literature concerning the use of non-thermal technologies for preservation of PJ. Therefore, this review focuses on PJ preservation by using non-thermal technologies. In conclusion, pomegranate is an economical crop that can justify the use of advanced non-thermal technologies for PJ preservation, as consumers' interest can offset the expenses associated with investments in alternative technological options and processing adjustments.